KEADILAN RESTORATIF SEBAGAI ALTERNATIF PENANGANAN KEKERASAN DALAM RUMAH TANGGA PERSPEKTIF HUKUM KELUARGA - Syeh Sarip Hadaiyatullah; Hendra Gunawan; Barani Panjaitan; Elvira Maharani Berutu (Yayasan Baitul Hikmah al-Zain, 2026)
Domestic violence constitutes a complex social and legal issue as it involves emotional, relational, and normative dimensions. Litigation-oriented approaches often generate further consequences in the form of family disintegration and deeper psychological trauma for both victims and perpetrators. Therefore, restorative justice is regarded as a relevant alternative in addressing domestic violence cases. This study employs a normative legal approach by examining statutory regulations, legal literature, and mediation practices oriented toward reconciliation. The analysis reveals that restorative justice has the potential to enhance victim protection while maintaining the continuity of family functions, although its implementation continues to face normative and structural challenges. Accordingly, the integration of family law values with restorative justice principles may offer a more humane, equitable, and relationship-oriented solution without neglecting the rights of victims.